A Tribute to the Danubius Hero Professor Benone Pusca - Michael, Steve O. (Danubius Universitas, 2023)
A day, not unlike today, the sun piercing through the clouds Heavens smiled upon the earth And bestowed a gift to the world named Benone Pusca Hard life he must live Communist Era he must brave Struggle for subsistence he must endure Struggle for freedom thrust upon him Through it all his spirit soared